Horizontal oder vertikal? Zur Zukunft des Finanzausgleichs in Deutschland - André W. Heinemann (Wirtschaftsdienst, 2012)
Nach der Föderalismusreform II wird immer deutlicher, dass mit Blick auf das Auslaufen der gegenwärtigen Grundlagen des Finanzausgleichs zum 31.12.2019 eine Föderalismusreform notwendig wird. Ins Visier kommt dabei zwangsläufig auch der Länderfinanzausgleich und sein Umverteilungsvolumen. Eine bloße Reform des Länderfinanzausgleichs im engeren Sinne in einem ansonsten unveränderten Gesamtsystem würde jedoch wieder einmal zu kurz greifen und erneut lediglich eine Symptomtherapie bedeuten. – – This article focuses on the background of the beginning debate on the German fiscal federalism reform. After a short description of the current vertical and horizontal fiscal relationships in Germany, the paper discusses general aspects of the relationship between two levels of state government in a federal system. Apart from a microeconomics-based explanation of the current horizontal revenue sharing dispute, findings from institutional economics support the thesis that a pure vertical fiscal equalisation scheme in Germany is possible and useful from an economic perspective. Finally, basic elements of a fiscal equalisation system reform are presented.
Keywords: H73; H77; 330; Finanzföderalismus; Reform; Horizontaler Finanzausgleich; Deutschland